Human Capital by Gender: A G20 and Selected Geographies Perspective - Barbara M. Fraumeni; Gang Liu; Shunsuke Managi (Institute of Labor Economics (IZA), 2024)
This working paper identifies the sources of human capital growth for the observation period 1990–2020 by region, gender and various determinants. It is a preliminary version of a forthcoming UNESCO/ Kyushu University Urban Institute Inclusive Wealth Report 2023 chapter. It focuses on five important country groups by gender - Asia, Africa, Latin America, the G20, and the EU - to highlight the differences between them. Human capital per capita varies significantly across countries in each group. Education and human capital is unevenly distributed among males and females, although both total and per capita human capital have grown over time in almost all countries. The paper concludes that attention must be paid to what has happened to the world's gender-disaggregated levels of education and human capital per capita over time. The future sustainability of nations and the well-being of individuals within nations depend on the continuation of historical progress.
Keywords: I21; J16; J24; O57; 330; human capital; country wealth; gender; country groups